2018
DOI: 10.1186/s12889-018-5804-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social determinants on antiretroviral therapy access and outcomes entering the era of universal treatment for people living with HIV in Italy

Abstract: BackgroundSocial determinants are known to be a driving force of health inequalities, even in high income countries. Aim of our study was to determine if these factors can limit antiretroviral therapy (ART) access, outcome and retention in care of people living with HIV (PLHIV) in Italy.MethodsAll ART naïve HIV+ patients (pts) of Italian nationality enrolled in the ICONA Cohort from 2002 to 2016 were included. The association of socio-demographic characteristics (age, sex, risk factor for HIV infection, educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…This might be due to literate patients having work capacity, financial resources, and access to quality health care. Patients in the middle-aged group were significantly decelerating time to immunological deterioration compared with those older patients, a finding that is in accordance with the literature [40,41], which noted that middle-aged adults experienced higher rates of CD4 recovery than the elderly. Furthermore, patients with many sex partners were significantly decelerating the recovery from severe to advanced stages compared with those with no sexual partner.…”
Section: Discussionsupporting
confidence: 90%
“…This might be due to literate patients having work capacity, financial resources, and access to quality health care. Patients in the middle-aged group were significantly decelerating time to immunological deterioration compared with those older patients, a finding that is in accordance with the literature [40,41], which noted that middle-aged adults experienced higher rates of CD4 recovery than the elderly. Furthermore, patients with many sex partners were significantly decelerating the recovery from severe to advanced stages compared with those with no sexual partner.…”
Section: Discussionsupporting
confidence: 90%
“…Factors such as psychiatric disorders, cognitive impairment, social stigma, substance abuse, and volatile housing can prevent optimal adherence [ 19 , 20 ]. Burch et al [ 21 ] found clear associations between markers of the social determinants of health and HIV outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the effects of age are larger for a patient being in the "normal and mild" immunological stage than that of a patient being in the "normal" immunological stage. Previous studies [43,44] also reported that middle-aged adults experienced higher rates of CD4 recovery. Contrary to our findings, an inverse relationship between the age of the patient and CD4 count recovery has been reported in previous studies [45][46][47].…”
Section: Discussionmentioning
confidence: 71%